Oral Tradition and ICT as Strategies to Foster Writing in Basic Education (Docentes 2.0 Journal, 2026)
Written expression is a fundamental competence in students' academic and personal development, as it enables them to communicate ideas clearly and to resignify culture in contemporary society. This study aimed to explore how oral tradition, through stories, myths, and legends, can become a didactic strategy to strengthen written production in elementary school students, with the support of EdiLim software. The research followed the humanist paradigm, with an interpretive method, a qualitative approach, a thematic narrative design of a documentary, bibliographic-analytical type, and a cross-sectional scope. The population consisted of fifth-grade students from the San Mateo Educational Institution, who participated in workshops, interviews, and diagnostic surveys. The results showed that the integration of oral tradition with EdiLim increased motivation toward written production, improved textual coherence and cohesion, and strengthened students' cultural identity. The study also identified strengths in creativity and weaknesses related to the lack of prior strategies for written production. In conclusion, oral tradition, in connection with ICT, constitutes a pedagogical strategy that favors meaningful written expression, cultural reflection, and active student participation, and contributes to the construction of inclusive and contextualized education.
Keywords: Oral tradition and ICT; strategies; promoting writing; basic education